Percutaneous or surgical tracheotomy when, why, and selection criteria (Annals of Medical Research, 2021)
Aim: Tracheotomy is one of the most frequent procedure especially in the intensive care units (ICU). And the major indication is prolonged respiratory support. Tracheotomy is a procedure for patients who need prolonged mechanical ventilation support or airway protection. By this way, the respiratory care and weaning from mechanical ventilatory support become easier and comfortable. Tracheotomy improves patient tolerance, reduces the need for sedation, avoids laryngeal irritation, enhances nursing care, reduces dead space. Among the ICU patients, 8- 24% of all, undergo tracheotomy procedure. This decision is individually based on the risk and benefits of tracheotomy versus prolonged intubation and also the consent of the patient's relations and expected clinical outcomes. But there is stil no consensus about the timing of the procedure. Clasically, the most considered opinion for tracheotomy in patients that are unable to wean from invasive ventilation within 10-14 days of intubation and should be planned under optimal conditions. The tracheotomy range increased over the last decade. But there is stil no consensus about the optimal timing for procedure, criterias for selection of patients, type of technique and timing of decannulation. The most common, traditional method is open surgical approach; performed in the operating room. Percutaneous technique is relatively simple to perform. And has a shorter procedure time. Percutaneous tracheotomy has become a popular, cost-effective, quick, simple and safe alternative to surgical tracheostomy. There is not an optimal tracheostomy, the physician should choose the best technique according to the patient and at the right time.